Energy and Daylighting Evaluation of Integrated Semitransparent Photovoltaic Windows with Internal Light Shelves in Open-Office Buildings. (21st December 2020) - Mesloub, Abdelhakim; Ghosh, Artira; Albaqawy, Ghazy Abdullah; Noaime, Emad; Alsolami, Badr M
Abstract : In modern architecture, highly glazed commercial buildings account for considerable amount of energy, specifically in cold and hot climates because of heating, cooling, and lighting energy load demand. Abatement of this high building energy is possible by employing semitransparent photovoltaic (STPV) window which has triple point advantages as they control the admitted solar gain and daylight and generates benign electricity. Integration of internal light shelves (ILS) to this STPV window assists in controlling visual comfort. Thus, this study aims to evaluate the impact of a nonuniform layout of double-glazing (DG) low-e STPV and DG low-E argon-filled clear glass integrated into a fully glazed open-office facade combined with ILS in cardinal orientations under Riyadh, London, Kuala Lumpur, and Algiers climates. Comprehensive energetic and radiance simulations were conducted to evaluate three groups of STPV configurations. The first group replaced the glazing area with amorphous silicon (a-Si) modules with different transparencies; the second and third groups changed only 75% and 50% of the glazing area, respectively, with STPVs integrated with the ILS. The results revealed that the integration of a-Si modules did not meet the visual comfort requirements but obtained the maximum saving in the east-west axis. It was also found that the optimum design on the south-facing facade with the nonuniform facade achieved 50% of STPV10 coverage in clear glazing windows combined with ILS; the energy saving ratios comparing the reference models were 76%, 83%, 65%, and 70% in Riyadh, London, Kuala Lumpur, and Algiers, respectively. Thus, the integration of STPVs with ILS is considered a more efficient way and effective solution to reduce the possibility of glare discomfort.